Do Cattle Egrets Bubulcus ibis in Sri Lanka migrate to breed? - Jayaratne, R. L.; Perera, Inoka C.; Weerakoon, D. K.; Kotagama, S. W. (My University, 2016)
The Cattle Egret Bubulcus ibis is a common wetland bird in Sri Lanka, and a common member of communal roosting sites of water birds throughout the country. It forages in grasslands, paddy fields, marshes, and garbage dumping sites (Kotagama & Ratnavira 2010). White-coloured Cattle Egrets show a golden buff on their back, neck, and head during the breeding season (Kotagama & Ratnavira 2010). Past studies have reported that some populations of Cattle Egrets are migratory, while others are dispersive (Telfair 2006). Cattle Egrets, in the southern plains of Australia, fly to winter areas—ranging from short distances, to more than 2000 km to Tasmania, and New Zealand (Maddock & Geering 1994). According to the studies done in India by Seedikkoya et al. (2005), and Kushlan & Hafner (2000), its populations in southern India appear to show local migrations in response to the monsoons. They move northward from Kerala, after June. Further, Rasmussen & Anderton (2005) noted that resident populations of the Cattle Egret, in Sri Lanka, were greatly increased by a winter influx. Being a widespread species in Sri Lanka, Cattle Egrets should be monitored closely, as migratory Cattle Egrets are sometimes attributed in the spreading of ticks, which may cause human, livestock, and wildlife diseases (Corn et al. 1993). Hence, this work was specifically carried out, in Sri Lanka, with two objectives: (a) To find out the monthly variation of the Cattle Egret’s population; and, (b) To identify its nesting heronries. Five roosting sites were selected for this purpose, from three different climatic zones: a Colombo site from the wet zone, sites in Kandy from the montane region, and in Anuradhapura from the dry zone (Fig. 1). Population counts, at selected roosting sites, were carried out from January 2013 to July 2015 by scan sampling. The number of individuals arriving at the roosts, between 1700 and 1830 hrs, were counted twice a month. Thirty-three heronries, comprising mixed-species, were observed during July–September, every year, from 2013 to 2015, throughout the island, to locate nesting Cattle Egrets (Fig. 1). These are the months when they disappear from their roosting sites for breeding. The maximum population of Cattle Egrets was recorded during the months of January, and February (Fig. 2). In March, Cattle Egrets began moulting into their breeding plumage, which peaked by the end of May—indicating breeding from June onwards. This is contrary to the observations of Harrison (2011), who report their nesting from December to May. Cattle Egret populations gradually decreased at roosting sites from March to June—no birds were observed in July, August, and September (Fig. 2). However, small groups of four to five birds in non-breeding plumage were observed in paddies and grasslands during these months. We found that though the number of individuals varies from roosting site to roosting site, from one non-breeding period to another, the total population of Cattle Egrets, excluding the Colombo site, remains relatively stable. We believe this indicates an internal movement of the birds from one roosting site to another.